Cyclic thermo-mechanical material modelling and testing of 316 stainless steel - Hyde, Christopher J.; Sun, W.; Leen, Sean B. (Elsevier, 2010)
A programme of cyclic mechanical testing of a 316 stainless steel, at temperatures of up to 600 °C under isothermal conditions, for the identification of material constitutive constants, has been carried out using a thermo-mechanical fatigue test machine (with induction coil heating). The constitutive model adopted is a modified Chaboche unified viscoplasticity model, which can deal with both cyclic effects, such as combined isotropic and kinematic hardening, and rate-dependent effects, associated with viscoplasticity. The characterisation of 316 stainless steel is presented and compared with results from tests consisting of cyclic isothermal, as well as in-phase and out-of-phase thermo-mechanical fatigue conditions, using interpolation between the isothermal material constants to predict the material behaviour under anisothermal conditions.